PERBANDINGAN ABNORMAL RETURN DAN VOLUME PERDAGANGAN SAHAM PADA PERUSAHAAN YANG MENGIKUTI INDONESIAN SUSTAINABILITY REPORTING AWARD (ISRA) - Putri Rahmatul Umi; Yeasy Damayanti; Wahidil Wahidil (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Riau, 2020)
This research studies the impact of Indonesian Sustainability Reporting Award (ISRA) 2011- 2015 announcement to abnormal return and trading value activity. The impact of award publication is whether there are some differences between abnormal return and trading value activity before and after ISRA announcement. The research samples are 42 companies accepted the appreciation of ISRA 2011-2015 period. The research data used is secondary data consists of daily stock closing prices and daily trading volume with the observation period seven days before and seven days after the announcement. The model used for the measurement of abnormal return is market-adjusted models. The hypothesis tested by Wilcoxon Signed Ranks Test. The results of this research proved that there is a difference of abnormal return before and after the announcement of ISRA 2011-2015. While the trading value activity there was no difference before and after the announcement of ISRA 2011-2015